Overview of surface to near‑surface atmospheric profles over selected domain during the QWeCI project - Aryee, J. N. A.; Amekudzi, L.K.; Atiah, W. A.; Osei, M. A.; Agyapong, E. (Meteorology and Atmospheric Physics, 2019)
An article published by Meteorology and Atmospheric Physics and available at https://doi.org/10.1007/s00703-018-0618-1